2016
DOI: 10.1021/acs.jafc.6b02543
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Induced a High Accumulation of Dietary Isoflavones and Expression of Isoflavonoid Biosynthetic Genes in Soybean (Glycine max) Leaves

Abstract: Dietary isoflavones, daidzein and genistein are of huge interest in the nutraceutical field due to their practical application to postmenopause complications. This study is the first report an efficient method to prepare isoflavone rich soybean leaves (soyleaves) which is an edible food stuff in Asian countries. The preharvest treatment of ethylene highly stimulated the level of isoflavone in soyleaves. Annotation and quantification of metabolites were determined by UPLC-Q-TOF-MS and HPLC. Phenolic metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 42 publications
6
58
1
1
Order By: Relevance
“…Peak detection was performed at 254 nm. The four isoflavones were identified as per the retention time, and their concentrations were calculated by comparing the peak areas of the samples with those of the standards using LCSolutions software (Shimadzu, Kyoto, Japan) …”
Section: Methodsmentioning
confidence: 99%
“…Peak detection was performed at 254 nm. The four isoflavones were identified as per the retention time, and their concentrations were calculated by comparing the peak areas of the samples with those of the standards using LCSolutions software (Shimadzu, Kyoto, Japan) …”
Section: Methodsmentioning
confidence: 99%
“…Because flavonols were not synergistically induced by the combination of herbivory and solar UV‐B radiation or after ACC application, our results suggest that only isoflavonoids are induced by ET alone (Figures , and ; Figures S3 and S4). Recently, a study have shown that both ethephon and ET induced isoflavonoids in potted soybean grown in a greenhouse (Yuk et al, ), suggesting the primary role of ET in the induction of certain defenses.…”
Section: Discusionmentioning
confidence: 99%
“…Also, ET applied exogenously or produced during pathogen infection or stink bug attack eliminates the JA‐SA antagonistic relationship, allowing the induction of both JA‐ and SA‐regulated defenses (Giacometti et al, ; Leon‐Reyes et al, ). Although few studies have focused on the effects of ET alone on plant defenses, recently, it has been suggested that ET can increase the production of isoflavonoids in soybean leaves (Yuk et al, ). Because it is not clear how solar UV‐B radiation synergistically increases chemical defenses in damaged leaves, we proposed that UV‐B radiation induces ET emission that increases the production of phenolic compounds and TPI in soybean leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Jiao et al (1987) found that light reduces ethylene formation. Yuk et al (2016) suggested that ethylene activates a set of structural genes involved in flavonoid biosynthesis. Here, we identified a total of 120 ERF TFs, representing the largest TF family in our transcriptome data.…”
Section: Transcription Factors Involved In Light-regulated Flavonoid mentioning
confidence: 99%